KEKERASAN TERHADAP PEREMPUAN MENURUT TINJAUAN AGAMA DAN SOSIOLOGI - Hasbi, Muhammad (AL-MAIYYAH : Media Transformasi Gender dalam Paradigma Sosial Keagamaan, 2017)
Islamic religion look into that God not create human being by differing. Islam explain that basically there not superioritas in meaning of kualitataif men to woman. As religion bringing equivalence mission, Islam affirm that most human being of glory is most them of taqwa to God. In the sosiological view, society assumed as social institute which reside in in balance is activity of human being pursuant to embraced norms with was and also held true and fasten role and also itself human being.That way also, in the sosiological view, society assumed as social institute which reside in in balance is activity of human being pursuant to embraced norms with was and also held true and fasten role and also itself human being In the eyes of sociology in action hardness of woman send to problem domicile and woman function. Besides leading into problem of movement, conception equivalence supported by feminism movement wish the existence of change especially in looking at role of woman, either in educational, economic, politics, law even religion.